2009
DOI: 10.1093/eurpub/ckp032
|View full text |Cite
|
Sign up to set email alerts
|

Staff reports of psychosocial climate at school and adolescents' health, truancy and health education in Finland

Abstract: school climate is associated with adolescents' health, wellbeing and received health education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 27 publications
1
46
1
9
Order By: Relevance
“…Similar findings have been found with respect to alcohol and drug use [14] and violence [13], but are unique in relation to risky motor vehicle use. Studies have also found an association between positive school climate and better emotional well-being, which was not replicated in this study [12]. These findings suggest that interventions that target the school climate and aim to improve the relational supports, and the safety and inclusion of students in schools, could improve health and well-being outcomes among students.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Similar findings have been found with respect to alcohol and drug use [14] and violence [13], but are unique in relation to risky motor vehicle use. Studies have also found an association between positive school climate and better emotional well-being, which was not replicated in this study [12]. These findings suggest that interventions that target the school climate and aim to improve the relational supports, and the safety and inclusion of students in schools, could improve health and well-being outcomes among students.…”
Section: Discussioncontrasting
confidence: 88%
“…This has been motivated by observational studies that have shown that a positive school climate is associated with better student outcomes such as better emotional well-being [12] and lesser violence [13] and substance use [14]. Teacher well-being is an integral part of the overall school climate.…”
mentioning
confidence: 99%
“…That is, teacher absenteeism may lead to deterioration of the psychosocial work environment at school (for example, by increasing the workload of other teachers) and, hence, increase student misbehaviour through the deterioration of pupils' motivation and increased feelings of psychological insecurity. Indeed, a poor psychosocial work environment, as perceived by teachers, has been associated with pupils' poorer health and increased truancy (Virtanen et al, 2009). Furthermore, pupils' reports of school dissatisfaction, an indicator of psychosocial environment, were associated with teachers' increased absence due to illness (Ervasti, Kivimäki, Puusniekka, et al, 2011).…”
Section: Tablementioning
confidence: 99%
“…1 Increasingly, attention has been placed on the importance of school climate as one domain of school environment beyond health policies and education that may have implications for student health outcomes. 6,7 …”
mentioning
confidence: 99%
“…School climate is based on patterns of students’, parents’, and school personnel’s experience of school life and reflects norms, goals, values, interpersonal relationships, teaching and learning practices, and organizational structures.” 8 More positive school climate is associated with fewer risky health behaviors (ie, alcohol use, reckless driving, and violence), 6 increased physical activity among girls, 9 and emotional well-being. 7 The association of school climate with positive health behaviors and emotional well-being suggests that school climate could also have an association with positive physical health outcomes. Indeed, an association of school climate with physical health symptoms has been documented, 7 but there are limited studies that have examined the association between school climate and obesity.…”
mentioning
confidence: 99%